PENGARUH KEMAMPUAN LITERASI MEMBACA TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIKA SISWA KELAS VIII SMP NEGERI 2 TIAKUR - Inuhan, Michael; Kurniati, Ratnah; Bonara, Arche Febry; Rupillele, Karolina (Program Studi Pendidikan Matematika (Kampus Kab. Maluku Barat Daya) Universitas Pattimura, 2024)
This research aims to describe the mathematical problem solving and reading literacy abilities of students in class VIII of SMP Negeri 2 Tiakur. Furthermore, this research was conducted to show whether or not there is an influence of reading literacy skills on students' mathematical problem solving abilities and to find out what form this influence takes. The data analysis used in this research is simple linear regression analysis with the general form . The variables in this research consist of the dependent variable (problem solving ability) which is denoted by Y and the independent variable (reading literacy) which is denoted by (X). The results of this research show that students' reading literacy influences students' problem solving abilities and the effect is positive with the regression equation .